A spinel ferrite catalyst for efficient electroreduction of dinitrogen to ammonia. Issue 36 (14th September 2020) - Tian, Ye; Shao, Xuehui; Zhu, Menghan; Liu, Wuming; Wei, Zhen; Chu, Ke
Abstract : The spinel ferrite NiFe2 O4 delivers high NRR activity and selectivity which is attributed to the surface Fe atoms that act as key NRR active sites for favorable N2 adsorption and H + suppression. Abstract : Ambient electrocatalytic N2 reduction reaction (NRR) provides an eco-friendly way for artificial NH3 production, while an efficient NRR process requires active and stable electrocatalysts. In this communication, we exploit the spinel ferrite NiFe2 O4 as a promising NRR catalyst. The developed NiFe2 O4 nanocubes/reduced graphene oxide (NiFe2 O4 /RGO) exhibited an appealing NRR performance with an NH3 yield of 32.2 μg h −1 mg −1 and a faradaic efficiency (FE) of 9.8% at −0.5 V (RHE), as well as a high catalytic durability. Mechanistic investigations revealed that the surface Fe atoms serve as key NRR active sites for favorable N2 adsorption and H + suppression. These findings may facilitate the understanding and exploration of Earth-abundant spinel ferrite catalysts for electrochemical dinitrogen fixation.